CsCYT75B1, a Citrus CYTOCHROME P450 Gene, Is Involved in Accumulation of Antioxidant Flavonoids and Induces Drought Tolerance in Transgenic Arabidopsis - Rao, Muhammad Junaid; Xu, Yuantao; Tang, Xiaomei; Huang, Yue; Liu, Jihong; Deng, Xiuxin; Xu, Qiang (Antioxidants, 2020)
CYTOCHROME P450s genes are a large gene family in the plant kingdom. Our earlier transcriptome data revealed that a CYTOCHROME P450 gene of Citrus sinensis (CsCYT75B1) was associated with flavonoid metabolism and was highly induced after drought stress. Here, we characterized the function of CsCYT75B1 in drought tolerance by overexpressing it in Arabidopsis thaliana. Our results demonstrated that the overexpression of the CsCYT75B1 gene significantly enhanced the total flavonoid contents with increased antioxidant activity in transgenic Arabidopsis. The gene expression results showed that several genes that are responsible for the biosynthesis of antioxidant flavonoids were induced by 2–12 fold in transgenic Arabidopsis lines. After 14 days of drought stress, all transgenic lines displayed an enhanced tolerance to drought stress along with accumulating antioxidant flavonoids with lower superoxide radicals and reactive oxygen species (ROS) than wild type plants. In addition, drought-stressed transgenic lines possessed higher antioxidant enzymatic activities than wild type transgenic lines. Moreover, the stressed transgenic lines had significantly lower levels of electrolytic leakage than wild type transgenic lines. These results demonstrate that the CsCYT75B1 gene of sweet orange functions in the metabolism of antioxidant flavonoid and contributes to drought tolerance by elevating ROS scavenging activities.